CAN INDIVIDUALS WITH KLINEFELTER SYNDROME HAVE OFFSPRING? - Trovó de Marqui, Alessandra Bernadete (Acta Biologica Brasiliensia, 2025)
Klinefelter syndrome (KS) is the most common genetic cause of male infertility. The frequencies of infertility and azoospermia amongst the KS individuals are >99% and >95%, respectively. However, in extremely rare cases, KS patients will have offspring. This study aims to present the results of five scientific articles (3 case reports and 2 original articles) on individuals with KS who had children. Our results indicate that there are relative paucity of data on this topic published in the literature, highlighting that biological parenthood in the SK individuals is exceedingly rare.